Alyxia Banks ex R.Br. in New Caledonia: a clarification of several species complexes, nomenclatural notes, and a description of three new species - Lannuzel, Guillaume; Munzinger, Jérôme; Vandrot, Hervé; Gâteblé, Gildas (Phytotaxa, 2024)
The genus Alyxia Banks ex R.Br. is partially revised for New Caledonia, with 31 species recognised. The species complex Alyxia tisserantii Montrouz. is discussed and divided into seven species with existing names, and the synonymy is updated accordingly. Alyxia loeseneriana var. macrocarpa Boiteau is elevated to species status due to new flowering material with the name A. paniensis Lannuzel nom. nov., stat. nov. created to accommodate it, due to the preexisting Alyxia macrocarpa Koord. Detailed study of Alyxia caletioides (Baill.) Guillaumin ex Däniker revealed it was in fact made up of two distinct taxa; a new separate species, Alyxia urceolata Lannuzel, sp.nov. is therefore described. Two new species are also described following their recent collection: Alyxia humboldtensis Lannuzel & Gâteblé, sp.nov. is restricted to the summit of Mount Humboldt, and Alyxia minimiflora Lannuzel, sp.nov. is known from schistaceous cliffs around Nouméa. Finally, several nomenclatural issues are discussed, and an updated key to the genus in New Caledonia is provided.